OCCUPATIONAL HAZARDS IN CONSTRUCTION INDUSTRY: CASE STUDIES FROM HOUSING AND CONSTRUCTION WORKERS AT ADDIS ABABA, ETHIOPIA - Tolera, Thewodros Bekele (International Journal of Research -GRANTHAALAYAH, 2016)
The status of occupational injuries in workplaces in general is ill defined in Ethiopia. Pocket studies indicate that occupational injury due to an unsafe working environment is increasing. Construction industries are growing industries region wise that has higher rate of work-related injuries. Knowing the associated factors of work-related injuries can be a critical step for improving the working condition of workers in the sector. Objective: This mini research aimed to evaluate occupational hazards and to describe factors affecting its happening among construction workers’ in Addis Ababa housing and construction project sites. Institutional based cross-sectional study design was employed to assess occupational injuries among randomly selected construction workers from June 30 –July 20, 2014. A structured questionnaire based interviews, work environment observation were used to collect the data. The response rate of this study was 82.7%. The majority of respondents were male which account 74.7% and 60 (96.8%) respondents were not using personal protective devices all the time while they are on duty. Out of the total participants, 67.7% of the workers experienced occupational injuries at least once in the last 12 months. Moreover, the three leading cause of injuries were puncture (21.0%) followed by hand injury (11.3%), and back pain (9.7%). Increased rate of work related injury in construction workers was observed and implementation of basic occupational health and safety services is required together with regular supervision to ensure and promote work place safety. So Preventive measures concerning functional occupational health and safety programs are essential to safeguard the health and safety condition of workforce in construction industries.